Investigation on conical separation vortex generated by swept shock wave/turbulent boundary layer interaction. (October 2022) - Zhou, Yong-yi; Zhao, Yi-long; Zhao, Yu-xin; He, Gang; Gao, Pu-yun
Abstract: To study the effects of Mach number, Reynolds number and deflection angle on the conical separation vortex generated by swept shock wave/turbulent boundary layer interaction, the experimental and numerical simulation methods are used. The Mach numbers are Ma = 2 . 95 and Ma = 4 . The deflection angles are 12 °, 15 ° and 18 ° . The incoming boundary layer thickness δ 0 . 99 is 4.6 mm, 23 mm and 115 mm. The evolution characteristics of the vortex, including the vortex core position, the vortex area and the vortex intensity, and the effects of Mach number, Reynolds number and deflection angle on them are analyzed. The results show that the core trajectory of the vortex is distributed along the rear shock foot line of the λ shock structure. The Reynolds number is the main factor affecting the separation vortex core. The vortex area increases linearly along the direction of the inviscid shock, and the Reynolds number and the Mach number both are the factors affecting the growth rate of the separation vortex. The vortex intensity increases linearly along the direction of the inviscid shock. The vortex intensity is mainly affected by the Mach number and the deflection angle, but is not affected by the Reynolds number. Highlights: The evolution law of conical separation vortex is studied. The effects of influencing factors on the evolution characteristics are analyzed. Flow field of swept shock wave/turbulent boundary layer interaction is visualized.